End-of-life decisions in perinatal care. A view from health-care providers - Patricia Grether; Rubén Lisker; Alvar Loria; Asunción Álvarez- (Instituto Nacional de Salud Pública, 2015)
Objective. To examine the opinions of a perinatal health team regarding decisions related to late termination of pregnancy and severely ill newborns. Materials and Methods. An anonymous questionnaire was administered to physicians, social workers, and nurses in perinatal care. Differences were evaluated using the chi square and Student's t tests. Results. When considering severely ill fetuses and newborns, 82% and 93% of participants, respectively, opted for providing palliative care, whereas 18% considered feticide as an alter- native. Those who opted for palliative care aimed to diminish suffering and those who opted for intensive care intended to protect life or sanctity of life. There was poor knowledge about the laws that regulate these decisions. Conclusions. Although there is no consensus on what decisions should be taken with severely ill fetuses or neonates, most participants considered palliative care as the first option, but feticide or induced neonatal death was not ruled out.